Pengaruh Peringatan Bahaya Merokok Pada Kemasan Rokok Terhadap Minat Beli Mahasiswa Universitas Nuku di Kota Tidore Kepulauan - Nurjana Samad; Akbar A. Koja; M. jufri Sukandi (Peneliti.net, 2023)
Cigarettes are toxic substances that give a relaxing and suggestive effect. Cigarettes have a cylindrical shape of paper measuring between 70 and 120 mm long, with a diameter of about 10 mm which contains chopped tobacco leaves. Cigarettes are usually sold in boxes or paper packages that fit easily into pockets. Currently, cigarette packaging includes pictures of the impact of consuming cigarettes. The image that appears is the result after someone smokes too much. Cigarette packs also display the words